Features of economic assessment construction of buildings with low power consumption - Kishchnko, T.; Gusarova, L.; Bolila, N. (Ways to Improve Construction Efficiency, 2018)
The article deals with the problems of the economic evaluation of the construction of buildings with low power consumption. The classification of buildings according to the level of low energy consumption is given and it is recommended to differentiate the economic assessment according to the class. It is noted that when choosing an optimal investment option for energy-efficient construction, it is necessary to take into account the amount of capital investments and current operational costs.